Real-time simulation of advanced manufacturing systems - Edinburg, Ari (My University, 1991)
In order to analyse and optimize the design and Operation of Advanced Manufacturing Systems (AMS) various simulation techniques are currently in use. However, these methods are' generally inflexible and are used off-line in this project report, a modular, modelling approach is adopted to investigate the requirements of shop floor device models which operate in real-time. The models when connected together, simulate the Operation of the AMS. A suitable technique for the development of these models is proposed. A simulation architecture to support the models is discussed. It is intended that the models are connected on-line to the AMS control system via a local Area Network (LAN). [Advantages and - applications of this approach to AMS simulation are discussed.
A project report submitted to the Faculty of Engineering. University of the Witwatersrand, Johannesburg, in Partial fulfilment of the requirements for the. degree of Master of Science in Engineering, Johannesburg. 1991
Keywords: Flexible manufacturing systems; Computer integrated manufacturing systems; Manufacturing processes--Computer simulation